2-Alkylquinolone alkaloid biosynthesis in the medicinal plant Evodia rutaecarpa involves collaboration of two novel type III polyketide synthases - Matsui, Takashi (J Biol Chem, 2017)
2-Alkylquinolone (2AQ) alkaloids are pharmaceutically and biologically important natural products produced by both bacteria and plants, with a wide range of biological effects, including antibacterial, cytotoxic, anticholinesterase, and quorum-sensing signaling activities. These diverse activities and 2AQ occurrence in vastly different phyla have raised much interest in the biosynthesis pathways leading to their production. Previous studies in plants have suggested that type III polyketide synthases (PKSs) might be involved in 2AQ biosynthesis, but this hypothesis is untested. To this end, we cloned two novel type III PKSs, alkyldiketide-CoA synthase (ADS) and alkylquinolone synthase (AQS), from the 2AQ-producing medicinal plant, Evodia rutaecarpa (Rutaceae). Functional analyses revealed that collaboration of ADS and AQS produces 2AQ via condensations of N-methylanthraniloyl-CoA, a fatty acyl-CoA, with malonyl-CoA. We show that ADS efficiently catalyzes the decarboxylative condensation of malonyl-CoA with a fatty acyl-CoA to produce an alkyldiketide-CoA, whereas AQS specifically catalyzes the decarboxylative condensation of an alkyldiketide acid with N-methylanthraniloyl-CoA to generate the 2AQ scaffold via C–C/C–N bond formations. Remarkably, the ADS and AQS crystal structures at 1.80 and 2.20 Å resolutions, respectively, indicated that the unique active-site architecture with Trp-332 and Cys-191 and the novel CoA-binding tunnel with Tyr-215 principally control the substrate and product specificities of ADS and AQS, respectively. These results provide additional insights into the catalytic versatility of the type III PKSs and their functional and evolutionary implications for 2AQ biosynthesis in plants and bacteria.